Neuropathy in lymphoma: a relationship between the pattern of neuropathy, type of lymphoma and prognosis?. Issue 7 (30th October 2007) - Viala, K; Béhin, A; Maisonobe, T; Léger, J-M; Stojkovic, T; Davi, F; Leblond, V; Bouche, P
Abstract : Background: Neuropathies associated with lymphoma (NAL) are rare and present a great clinical heterogeneity, making them difficult to diagnose and worsening their prognosis. Objectives: (1) To report the different patterns of NAL and discuss the mechanisms encountered; (2) to determine the relationship between a given type of lymphoma and a specific type of neuropathy; and (3) to assess the prognosis of NAL. Methods: Among 150 patients with lymphoma and neuropathy, we selected 26 in whom the neuropathy was not related to drug induced or IgM-antimyelin associated glycoprotein neuropathies. The pattern of neuropathy was defined in terms of its clinical and electrophysiological features. Neurological improvement, haematological remission and occurrence of death were taken into account to determine the prognosis. Results: 13 patients (50%) had a demyelinating polyneuropathy (PNP), seven (27%) had a radiculopathy linked to proximal root tumoral infiltration and six (23%) had an axonal multiple mononeuropathy (MM) related to distal lymphomatous infiltration or to paraneoplastic microvasculitis. Hodgkin's lymphoma was only associated with demyelinating PNP. High grade B cell lymphoma was strongly associated with radiculopathy. Neurological improvement was observed in 69% of patients with demyelinating PNP, 29% with radiculopathy and 50% with MM. Haematological remission was observed in 46% of patients with demyelinating PNP, 29% with radiculopathy and 83% with MM. Conclusions: Demyelinating PNP, the most frequently observed neuropathy in this study, had the best neurological prognosis. Chemotherapy combined with immune mediated treatment was the most effective treatment in this group. Identifying the type and mechanism of NAL is crucial in order to define the therapeutic strategy and improve the prognosis.